Photo-induced synthesis of nanostructured Pt-on-Au/g-C3N4 composites for visible light photocatalytic hydrogen production - Tang, Yanting; Huang, Jielin; Jiang, Manxiang; Yu, Jinpeng; Wang, Qi; Zhao, Jingjing; Li, Juan; Yu, Xin; Zhao, Junwei (Journal of materials science, 2020)
Nanostructured semiconductor composites are often considered as types of promising photocatalysts and display great prospects in visible light photocatalytic hydrogen production. In this work, nanostructured Pt-on-Au/PCN composites were synthesized by photo-induced synthesis strategy with exfoliated g-C 3 N 4 (PCN) nanosheets as starting materials and served in visible light photocatalytic hydrogen production. The prepared Pt-on-Au/PCN composites showed enhanced visible light absorption and photocatalytic hydrogen production performance. The visible light photocatalytic performance of Pt-on-Au/PCN composites is approximately 54.60 times of pristine g-C 3 N 4 and 3.61 times of Pt/g-C 3 N 4 composites, respectively. These findings could be mainly attributed to the formation of bimetal Pt-on-Au nanostructure for visible light harvesting and charge separation. Besides, possible photocatalytic mechanism of nanostructured Pt-on-Au/PCN composites for hydrogen production is proposed in detail. Current work also offers a new method to design and synthesize other types of metal-on-metal nanostructures for efficient semiconductor photocatalysis.